Pemanfaatan Aplikasi Canva Berbasis Fitur Storyboarding untuk Mengatasi Kesulitan Strukturasi Alur dalam Menulis Teks Fabel Siswa Kelas VIII SMP Negeri 15 Kota Bengkulu - Korniawan, Iwan; Andra, Vebbi; Friantary, Heny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to address the difficulties faced by eighth-grade students at SMP Negeri 15 in Bengkulu City in structuring the plot of fables through the use of the Canva app’s storyboarding feature. The main problems underlying this study are the students’ inability to arrange a sequence of events in a coherent manner, skipping the orientation stage and jumping directly to the resolution without any logical complications, as well as low active participation due to the use of conventional text-based learning media. This study is a Classroom Action Research (CAR) that adopts the Kemmis and McTaggart model, conducted over two cycles. Each cycle integrates the stages of planning, implementation of actions, observation, and reflection. The research subjects consisted of 30 eighth-grade students. Data were collected through a fable writing test, an activity observation sheet, and a student perception questionnaire, which were then analyzed using descriptive qualitative and quantitative methods. The results showed a significant improvement in the students’ ability to structure the plot of a fable. In the pre-cycle baseline condition, the class average score was only 62.7 with a classical mastery rate of 30.0% (9 students achieved mastery). After the implementation of the intervention in Cycle I, the average score increased to 71.5 with a classical mastery rate of 56.7% (17 students met the criteria). Strategic improvements in Cycle II yielded optimal results, with the class average score surging to 80.3 and the classical mastery rate reaching 86.7% (26 students achieved mastery), exceeding the established success target of 85%. Based on these findings, it was concluded that the use of the storyboarding feature on Canva effectively served as a visual scaffold that clarified the chronological sequence of events, stimulated critical imagination, and fostered students’ interest in learning literature in an interactive manner.